“Why has this new vaccine come and for what reasons?” key antecedents and questions for acceptance of a future maternal GBS vaccine: Perspectives of pregnant women, lactating women, and community members in Kenya - Rupali J. Limaye; Prachi Singh; Berhaun Fesshaye; Clarice Lee; Jessica Schue; Ruth A. Karron (Human Vaccines & Immunotherapeutics)
Group B streptococcus (GBS) is a leading global cause of neonatal sepsis and meningitis, stillbirth, and puerperal sepsis. While intrapartum antibiotic prophylaxis (IAP) is a currently available GBS disease prevention strategy, IAP is programmatically complex to implement, precluding use in low- and middle-income countries. In Kenya, 2% of stillbirths are attributable to GBS infection. Two maternal GBS vaccines are in late-stage clinical development. However, licensure of a maternal GBS vaccine does not translate into reduction of disease. We conducted 28 in-depth interviews with pregnant people, lactating people, and community members across two counties in Kenya to better understand the attitudes and informational needs of primary vaccine beneficiaries. We identified two emerging themes from the data. The first focused on antecedents to maternal GBS vaccine acceptability. The most common antecedents focused on the vaccine’s ability to protect the baby and/or the mother, followed by community sensitization before the vaccine was available. The second key theme focused on questions that would need to be addressed before someone could accept a maternal GBS vaccine. Three key categories of questions were identified, including vaccine safety compared to vaccine benefits, who gets the vaccine, and how the vaccine works. Realizing the potential benefits of a future GBS maternal vaccine will require a multifactorial approach, including ensuring that communities are aware of GBS-related harms as well as the safety and effectiveness of a maternal GBS vaccine. Our study contributes to informing this multifactorial approach by elucidating the attitudes and concerns of key populations.